Perancangan User Interface dan User Experience untuk Platform Kursus Online Menggunakan Metode Design Thinking dan Lean UX - Nurmalasari, Elis; Nugroho, Imam Maruf; Totohendarto, Moch. Hafid (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2023)
XYZ writing community is a community that was formed virtually in 2018 in Jember,East Java. The XYZ Writing Community conducts routine activities, namely holdingclasses on writing every one week twice through the WhatsApp chat platform only.From this problem, it can be seen that the learning system is less effective so that acontainer is needed to accommodate this. Making UI and UX designs will be donefirst using the Design thinking and Lean UX methods. The design results will be testedusing the User Experience Quisionnaerie (UEQ) method. Based on the design methodand testing method used to conduct this research. The distribution of questionnaires atthe Test stage of design thinking to 20 respondents obtained the results of designing anonline course website design in the field of writing using the UEQ method is aboveaverage with a "good" assessment based on the brenchmark diagram. The mean valueon the UEQ scale is above 1 with the highest mean value on the attractiveness scale of1.92 points and the lowest value is on the Novelty scale of 1, 26 points. From theseresults it can be said that the results of UI and UX design design are quite good andquite acceptable to users.